Manipulation of Lewis acid–base complexation in the Zr-centered quaternary system for monodisperse spherical zircons. Issue 8 (15th April 2021) - Peng, Shan; Chen, Zhongqiu; Huang, Qing; Xia, Xiaohong; Wang, Zhuo; Huang, Zhongbing; Homewood, Kevin P.; Gao, Yun; Lei, Binglong
Abstract: Zircon (ZrSiO4 ) is a distinctive material widely investigated and applied for its superb physicochemical advantages. To date, great challenges remain in the synthesis of high-quality zircon powders for their stringent crystallization requirements at elevated temperature and inherent preferential growth along the [200] direction. Herein we, for the first time, present monodisperse spherical zircon (MSZ) powders synthesized via a facile one-step hydrothermolysis at 200 °C by rationally manipulating the Lewis acid–base complexation of zirconium with competitive ions (Lewis basic R ligands) in a Zr–OH–R–F quaternary system. Systematical investigations were revealed encircling the complexation of Zr 4+ with the R ligands from various sources, which involve the adjusting acids (HR), Zr/Si reactants and halogen-containing mineralizers. Sufficient acidity from the adjusting acid and weak enough Zr–R affinity are confirmed as two paramount factors modulating the crystallization and growth of high-quality MSZ crystals, which undergo a unique metamorphic morphological transition from monolayered, to multilayered, to donut-shaped and ultimately to micrometer-sized spherical particles. The hydrothermal zircons are first confirmed as Zr-deficient (Zr/Si ratios <1.0) zirconium silicates as (ZrO4 )1–x Si[(OH)1–y ·Ry ]4x, rather than the Si-deficient Zr(SiO4 )1–x [(OH)·R]4x as initially proposed and hitherto generally accepted. The MSZ powders exhibit fair thermal stability and terrific monodispersity even after calcination at 1100 °C, superior photoreflectance and much lower thermal conductivity (0.18–0.48 W m −1 K −1 ) over non-spherical zircons. The novel MSZ powders provide arresting prospects to extend the applications of zircon in many traditional and emerging fields.